Remains of an intricately carved doorframe - Temples of India Project Team (Jio Institute, 2024)
In the Baroli group of temples, remains of an intricately carved doorframe can also be found, very close to the torana (ornamental gateway). The doorframe depicts divine figures which include Shiva, Brahma and Vishnu, along with river goddesses, navagrahas (nine planets), saptamatrikas (seven mother goddesses), and dvarapalas (door guardians).